Different Cardiovascular Responses to a Resistance Training Session in Hypertensive Women Receiving Propanolol Compared with Normotensive Controls - Fabiano Moraes Miguel; Luis Alexandre Grings; Guilherme Borges Pereira; Richard Diego Leite; Amilton Vieira; Nuno Manuel Frade de Sousa; Roberto Simão; Jonato Prestes (The Scientific World Journal)
The aim of the present study was to compare the responses of blood pressure, heart rate, and rate-pressure product of hypertensive women using beta-blockers with healthy controls during resistance exercise (by the end of the concentric phase of the contractions) and in the postexercise period (5 and 30 minutes after). Ten untrained normotensive women (N) and 10 mildly hypertensive females receiving 40 mg/day of propanolol (H) were selected. Three sets of 10 repetitions at 80% of 10 repetitions maximum with 30 s rest interval were performed on the leg press exercise. The H group exhibited lower systolic blood pressure after the second set compared with N. Heart rate and rate-pressure product were lower in H in all analyzed periods compared with N. Propanolol attenuates the cardiovascular response to a leg press resistance exercise in mildly hypertensive women.